PENERAPAN MANAJEMEN PRODUKSI PROGRAM PAGI INDAH DI RADIO TELSTAR 102.7 FM DALAM MEMPERTAHANKAN PENDENGARNYA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This study discusses the Application of Production Management for the Pagi Indah Program on Telstar Radio 102.7 FM. The aim is to find out the Pagi Indah production management program, including Pre Production, Production, and Post Production. Apart from that, it is also to analyze the solutions made by Telstar FM Radio in overcoming the challenges faced in the discussion about the supporting and inhibiting factors of the Pagi Indah production program. This type of research is descriptive qualitative, and the research informants are experts, the Pagi Indah program crew, and the Pagi Indah program listeners. As for the data collection method by observing (observations), interviews, and documentation. Data processing techniques and data analysis were carried out by searching and systematically compiling the data obtained through Miles and Huberman's qualitative data analysis model. The results of this study show that. 1) The production process of the Pagi Indah Program includes elements of production management that are applied, namely planning or planning, Organizing which is applied to the pre-production stage, Mobilization, Coordination and Motivation which is applied to the production stage, then Communication and Leadership which is applied to the three stages of production at once namely Pre Production, Production, and Post Production. Meanwhile, Supervision is applied to the Production and Post Production stages. 2). The obstacles and challenges faced by the Pagi Indah Program are the lack of human resources and challenges in contacting resource persons. The Pagi Indah crew program overcame these obstacles and challenges by improving the quality of its human resources and providing ideas by preparing several resource options as a solution to the challenge of contacting sources.